THE ESSENCE OF PROCESSES OF GLOBALIZATION, GLOBALISM AND SUSTAINABLE DEVELOPMENT - Anorov Rasulberdi Shomirza o'g'li; Mustafayev Jafar Shomirzayevich (Лучшие интеллектуальные исследования, 2024)
In order to create a clearer picture of the present era, it is important to consider that the world history until the beginning of the 20th century consisted of civilizations that developed independently and did not seriously affect each other. Today, the world has changed significantly as a result of the active integration of all aspects of society over the last hundred years and has become a whole organism. As a result of this, serious changes began to take place in the social consciousness of some peoples and all humanity, marked by global processes and general (world-wide) problems caused by them. It became clear that the world community has entered a new stage of its development, which differs from the previous stages not only in the scale of changes, but also in the level of activity and its universal nature